Perigenital necrotizing soft tissue infection caused by Aerococcus urinae - Andreas Forsvall; Magnus Wagenius; Magnus Rasmussen (IDCases, 2019)
Aerococcus urinae can cause severe invasive infections emanating from the urinary tract especially in older males with comorbidities. Here we describe a case of an 80 year-old man with multiple comorbidities presenting with a peri-penile abscess and signs of severe infection. Upon incision A. urinae was isolated in pure culture and the infection was cured by a combination of drainage and antimicrobials. This case demonstrates the potential of A. urinae to cause severe soft tissue infections in predisposed individuals. Keywords: Aerococcus urinae, Pergenital infection, Abscess